2009
DOI: 10.1111/j.1365-294x.2009.04095.x
|View full text |Cite
|
Sign up to set email alerts
|

Community composition, host range and genetic structure of the fungal entomopathogen Beauveria in adjoining agricultural and seminatural habitats

Abstract: Although intensively investigated for biological control of insect pests, little is known about the ecology of the fungal entomopathogenic genus Beauveria in natural or agricultural habitats. In this study, we used molecular phylogenetic and genotypic information to infer species diversity, reproductive potential and genetic structure of Beauveria occurring within a single arable field and bordering hedgerow in Denmark. Isolates were sampled from cultivated field and hedgerow soils, from insects harbouring lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 47 publications
12
121
0
7
Order By: Relevance
“…It infects a variety of insects from different orders and has the potential for insect pest control (Meyling et al, 2009). B. bassiana based mycoinsecticides are used against agricultural, veterinary and medical insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…It infects a variety of insects from different orders and has the potential for insect pest control (Meyling et al, 2009). B. bassiana based mycoinsecticides are used against agricultural, veterinary and medical insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…coluzzii). shown that B. bassiana is not monophyletic, however it is composed of several cryptic species that are morphologically identical (Ghikas et al, 2010;Meyling et al, 2009;Rehner et al, 2006). For instance, Ghikas et al (2010) described seven phylogenetic clusters in B. bassiana that consisted of isolates which did not show any geographic distribution but had common climate characteristics, and studies from Meyling et al (2009) found isolates that were distributed in five clusters in a particular hedgerow habitat.…”
Section: Discussionmentioning
confidence: 99%
“…shown that B. bassiana is not monophyletic, however it is composed of several cryptic species that are morphologically identical (Ghikas et al, 2010;Meyling et al, 2009;Rehner et al, 2006). For instance, Ghikas et al (2010) described seven phylogenetic clusters in B. bassiana that consisted of isolates which did not show any geographic distribution but had common climate characteristics, and studies from Meyling et al (2009) found isolates that were distributed in five clusters in a particular hedgerow habitat. Furthermore, a comparative genomic study of seven isolates of the plant pathogen Penicillium expansum showed that the genetic diversity found was between 1.27-7.13 SNPs/kb (Julca et al, 2016), while in two isolates of Aspergillus niger it was on average 7.8 SNPs/kb (Andersen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations